Transformasi Budaya Sekolah melalui Disiplin Positif dan Deep Learning untuk SDGs: Studi Kasus di SMP Negeri 2 Mranggen - Maria Ulfah; Widya Kusumaningsih; Nurkolis Nurkolis; Ismaila Ousman Jeng; Artika Wina Fitriani (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2025)
This research aims to examine the transformation of school culture through the implementation of positive discipline and deep learning strategies in order to support the achievement of the Sustainable Development Goals (SDGs), particularly SDG 4 on quality education. This study was conducted at SMP Negeri 2 Mranggen using a mixed-method approach and case study design. Data were collected through in-depth interviews, participatory observations, documentation, and questionnaires, involving the principal, teachers, and students as participants. The research results show that the planned and consistent implementation of positive discipline successfully builds a supportive, inclusive school climate and encourages individual responsibility. Meanwhile, the deep learning approach in the learning process strengthens student engagement, critical thinking, and collaboration in line with sustainability values. The transformation of school culture is manifested in the form of changes in values, interaction patterns, and more humanistic pedagogical practices. This research recommends the importance of integrating SDG values into school culture management through strengthening teacher capacity and transformative school leadership.